Proposed nano-scale sensing transducer using nano-waveguide for dynamic measurement applications - Keerayoot Srinuanjan; Yusaku Fujii; Panuwat Chaiyachet; Preecha P. Yupapin (My University, 2009)
We propose a new concept of a nano-sensing transducer system using a nano-waveguide. The small change in physical quantity affects to the change in device parameters such as refractive index or length which is relatively absorbed and observed by the resonant signal. In principle, the stored light pulse at the specified wavelength is generated by using a soliton propagating within the input ring resonators, whereas a resonant signal can be stored within the nano-waveguide, i.e. a transducer, which is formed the sensing ring device. The induced change in the resonant signal is occurred, and can be detected by using the wavelength domain detector (optical spectrum analyzer). Such a proposed device is suitable to perform the measurements in the nano-scale regime such as force, stress and temperature.
Keywords: SIGNAL (programming language); Waveguide; Photonic and Optical Devices